2015
DOI: 10.4081/aiua.2015.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Is routine ureteral stenting really necessary after retrograde intrarenal surgery?

Abstract: Routine double-J stent insertion after RIRS is not essential since it increases costs, morbidity and operation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
(16 reference statements)
0
10
1
2
Order By: Relevance
“…It has been reported that stenting after ureteroscopic stone management caused longer operative time [6]. However stenting after FURS led to the shorter operative times in the previous research [3], in our study operative time was longer in group 1.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…It has been reported that stenting after ureteroscopic stone management caused longer operative time [6]. However stenting after FURS led to the shorter operative times in the previous research [3], in our study operative time was longer in group 1.…”
Section: Discussioncontrasting
confidence: 44%
“…Nevertheless, a few studies have investigated the effect of intra-operative D/J stent placement on the stone-free rate following additional treatment. It was shown that D/J stent insertion could lessen the pain in FURS, although there was no benefit for stone free-status at first postoperative month [2,3]. However ureteral stent could be used for pain relief with a shorter operative time [10].…”
Section: Discussionmentioning
confidence: 99%
“…The primary purpose of stent insertion is to prevent ureteral stricture, accelerate healing, and facilitate stone passing 16 . On the other hand, stent insertion increases the possibility of urinary tract infection, dysuria, pollakiuria, hematuria, and may require repeated cystoscopy in cases of stent migration and need for extraction 17 . Stent insertion before ESWL does not eliminate the need for intervention in the management of SS 18 .…”
Section: Discussionmentioning
confidence: 99%
“…[46] In a series of 319 uncomplicated patients undergoing RIRS without previous stenting, 11.9% of the them needed urgent stenting; and male sex and stone located in the proximal ureter were found to be risk factors. [47] Ozyuvali et al [48] reported that no stenting was needed after RIRS as it increased the cost, morbidity and operation time in their study including 162 renal units. On the other hand, they found higher postoperative pain scores in patients with stones larger than 15 mm or located in renal pelvis.…”
Section: Postperative Double-j Stent Insertionmentioning
confidence: 99%